One month of you - Ewart, Suzanne (Sourcebooks Landmark, 2023)
"When Alec asks Jess out, she knows it won't work. Is Alec charming? Of course. Attractive? Definitely. Can she not stop thinking about him...yes, but that's also the problem. Because Jess has rules. And the first? Don't fall in love. What no one knows is that Jess has inherited Huntington's disease from the mother that she cares for. And while witnessing her own future play out, Jess has learnt to keep everyone and everything at arm's length. But Alec is determined to break down those barriers. When she finally tells him why they have no future, he proposes a different option--just one month together. One month to date. One month to live. One month to fall in love. But as Jess grows closer to Alec, she knows she has to end it. It's better that he is hurt now rather than heartbroken later, isn't it? "--